The role of vitamin D in menopausal women’s health - Mei, Zhaojun; Hu, Hong; Zou, Yi; Li, Dandan (Frontiers in Physiology, 2023)
Vitamin D (VD) is known to play an important role in the maintenance of calcium homeostasis and bone metabolism. In recent years, there has also been a growing interest in Vitamin D for health issues beyond the bones. Menopausal women are at risk of reduced bone density and increased risk of fracture due to a decline in estrogen levels. There is also an increased risk of cardiovascular disease, diabetes and hyperlipidaemia due to impaired lipid metabolism. The menopausal and emotional symptoms due to menopause are also increasingly prominent. This article summarizes the role of Vitamin D in menopausal women’s health, including the effects of Vitamin D on skeletal muscle, cardiovascular disease, Genitourinary Syndrome of Menopause (GSM), cancer and emotional symptoms. Vitamin D regulates the growth of vaginal epithelial cells and alleviates genitourinary tract problems in menopausal women. Vitamin D also modulates immune function and influences the production of adipokines. Vitamin D and its metabolites also have an anti-proliferative effect on tumour cells. This narrative review, by summarizing recent work on the role of Vitamin D in menopausal women and in animal models of menopause, aims to provide a basis for further development of the role of Vitamin D in the health of menopausal women.